A review of the species in the Apogon fasciatus group with a description of a new species of cardinalfish from the Indo-West Pacific (Perciformes: Apogonidae) - Fraser, Thomas H. (Zootaxa, 2005)
Nine nominal, Indo-West Pacfic species are treated: Apogon fasciatus (White, 1790), Apogon quadrifasciatus Cuvier in Cuvier & Valenciennes, 1828, Apogon monogramma Günther, 1880, Apogon septemstriatus Günther, 1880, Apogon evanidus Fowler 1904, Apogon elizabethae (Jordan & Seale, 1905), Apogon quinquestriatus Regan, 1908, Apogon kiensis Jordan & Snyder, 1901 and Apogon bryx Fraser, 1998. Four species treated as valid have VII first-dorsal spines: Apogon fasciatus with two brownish stripes on each side of the head and body to caudal peduncle and a faint, variable stripe along a portion of the lateral-line, 16 (15) pectoral-fin rays, and 14–17 (12, 13 or 18) gill rakers, Apogon quinquestriatus with four brownish stripes on each side of head and body, two reaching the caudal peduncle, 15 pectoral-fin rays, and 15 gill rakers, Apogon septemstriatus with three brownish stripes on each side of head and body, three reaching the caudal peduncle, 14 (13) pectoral-fin rays, and 14–16 gill rakers, Apogon pleuron, new species, with two brownish stripes on each side of head and body reaching the caudal peduncle, ventral edge of midlateral stripe with vertical bars, 15 (14 or16) pectoral-fin rays, and 17–20 (15, 16 or 21) gill rakers. Two species treated as valid have VI first-dorsal spines: Apogon bryx with three brownish stripes on each side of head and body, two reaching the caudal peduncle, 14–15 pectoral-fin rays, and 22–23 (21 or 24) gill rakers, Apogon kiensis, with two brownish stripes on each side of head and body reaching the caudal peduncle, 14–15 pectoral-fin rays, and 16–18 (15 or 19-20) gill rakers. The long recognized name, Apogon quadrifasciatus, is synonymous with Apogon fasciatus.